La salud pública se da a conocer: publicaciones sanitarias del Estado argentino, 1946-1950 - Ramacciotti, Karina Inés (2011)
The objective of this article is to analize the Argentinian’s Archivos de la Secretaría de Salud Pública (Archives of the Secretary of Public Health) between 1946 and 1950. The interest for this magazine lies in the accomplishment of two objectives: it was a vehicle of disclosure of scientific articles inside the medical community; also it helped letting know the actions about sanity of the government and the political ascent of health minister, the neurosurgeon Ra​món Carrillo. This pages allow to understand the organization and institutional dynamics of the state and its agencies and, in parallel, think how was built, historically, the public health as a social right.